PENDIDIKAN ANAK DALAM KELUARGA; TELAAH EPISTEMOLOGIS - Hasan Baharun (Nurul Jadid University, 2016)
Education is the largest field of investment in building and shaping men(insanul kamil). Education touches are believed capable of forming a hu-man resources civilized and qualified. The family as an educational insti-tution first and foremost for children, has a considerable role in realizingthese ideals. The family as an institution has a function that is important inshaping personalities, social, religious attitudes of children. Error interac-tions within families due to less optimal family members in carrying outtheir roles and functions of each can give rise to various problems in thefamily. Kids are the most important asset in a family, religion and nation ofIndonesia. Therefore, Islam as a religion that rahmatan lil Alamin payingattention and signs in the implementation of education within the family.The role of parents and families have a tremendous impact on the growthand development of children.